Improvements in sleep quality and fatigue are associated with improvements in functional recovery following hospitalization in older adults - Arentson-Lantz, Emily J.; Deer, Rachel R.; Kokonda, Manasa; Wen, Chelsey L.; Pecha, Thomas A.; Carreon, Samantha A.; Ngyen, Trung M.; Volpi, Elena; Nowakowski, Sara (Frontiers in Sleep, 2022)
Introduction. Poor sleep quality, a frequent problem in older adults, has been shown to be associated with reduced physical function and wellbeing. However, little is known about the relationship between sleep quality and the recovery of physical function following hospitalization. Thus, we conducted this study to examine the association between sleep quality and functional recovery after an acute hospitalization in community dwelling older adults. Material and methods. Older adult patients (N=23, mean age= 74 ± 9 years) were recruited during an acute hospitalization (average length of stay 3.9 days) with a cardiovascular (56%), pulmonary (22%), or metabolic (13%) admission diagnosis. Objective physical function was measured using the Short Physical Performance Battery (SPPB) and self-reported function was assessed with Katz Index of Independence in Activities of Daily Living (ADL) and Lawton Instrumental Activities of Daily Living Scale (IADL). Sleep quality was measured using Pittsburgh Sleep Quality Index (PSQI) global score and Iowa Fatigue Score (IFS). Testing was performed prior to discharge (baseline) and 4-weeks post-discharge (follow-up). Results. Regression models showed PSQI Subjective Sleep Quality change scores from baseline to 4-week follow-up predicted a change in ADL (β=-0.22); PSQI Use of Sleep Medications change scores predicted a change in SPPB Total (β=1.62) and SPPB Chair Stand (β=0.63); IFS change scores predicted SPPB Total (β=-0.16) and SPPB Chair Stand performance (β=-0.07) change scores. Discussion. For older adults, changes in sleep medication use, daytime dysfunction, and fatigue were associated with improvements in functional recovery (including physical performance and independence) from acute hospitalization to 4-week follow-up. These results suggest that interventions focused on improving sleep quality, daytime consequences, and fatigue might help enhance physical functioning following hospitalization.